Smart Camera Design Algorithms, Architectures, and Art - Wolf, Marilyn (Springer International Publishing, 2018)
This book describes the algorithms and computer architectures used to create and analyze photographs in modern digital cameras. It also puts the capabilities of digital cameras into context for applications in art, entertainment, and video analysis. The author discusses the entire range of topics relevant to digital camera design, including image processing, computer vision, image sensors, system-on-chip, and optics, while clearly describing the interactions between design decisions at these different levels of abstraction. Readers will benefit from this comprehensive view of digital camera design, describing the range of algorithms used to compose, enhance, and analyze images, as well as the characteristics of optics, image sensors, and computing platforms that determine the physical limits of image capture and computing. The content is designed to be used by algorithm designers and does not require an extensive background in optics or electronics. Presents the full range of modern digital camera algorithms: image capture, enhancement, and analysis; Analyzes the interactions between algorithm design, sensor and optics characteristics, and computational capabilities; Provides a unified view of image and video capture and analysis in modern cameras, given that the traditional distinction between still and moving image cameras has largely disappeared.